Perlindungan Form Website Pada Framework Flask Dengan Metode Regular Expression - Mahendra Chevro Susanto (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
This research aims to find out the use of regular expression methods in protecting website forms on the flask framework. The regular expression pattern used in this research is [^A-Za-z0-9@]. In this study, testing was carried out using the black box testing method Equivalence Partitioning technique to create test criteria in website form input. The results of black box testing produce two expectations, namely "Secure Data" and "Insecure Data". The results of this study indicate that the use of the Regular Expression method in website form protection is quite effective. Regular Expression makes it possible to validate the data inputted by users and prevent malicious input by removing invalid characters.